Causal association between employment transitions and suicide in Australia - Swikar Poudel; Sandro Sperandei; Andrew Page; Yi Guo (Scientific Reports)
Abstract Suicide remains a significant public health concern globally, with unemployment, financial hardship, and employment transitions cited as contributing factors. However, their causal association remains unclear. This study investigates the causal association between employment transitions and suicide in Australia from 2009 to 2018, utilising Convergent Cross Mapping (CCM), a dynamical systems approach. Employment transitions were categorised into positive transition, no transition, and negative transition groups, representing changes in employment status. Initial analysis of raw data suggested all three groups showed causal association to suicide. However, detrending the time series revealed that only negative transition maintained a significant causal association with suicide, while no transition and positive transition showed no causal association. These findings emphasise the critical association of employment instability on mental health and the importance of stable or improving employment conditions in suicide prevention. The study discusses the need for targeted interventions to mitigate the adverse effects of employment downturns.